2020
DOI: 10.1038/s41598-020-73662-4
|View full text |Cite
|
Sign up to set email alerts
|

Foxd4l1.1 negatively regulates transcription of neural repressor ventx1.1 during neuroectoderm formation in Xenopus embryos

Abstract: Neuroectoderm formation is the first step in development of a proper nervous system for vertebrates. The developmental decision to form a non-neural ectoderm versus a neural one involves the regulation of BMP signaling, first reported many decades ago. However, the precise regulatory mechanism by which this is accomplished has not been fully elucidated, particularly for transcriptional regulation of certain key transcription factors. BMP4 inhibition is a required step in eliciting neuroectoderm from ectoderm a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
32
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(34 citation statements)
references
References 64 publications
2
32
0
Order By: Relevance
“…[13]. In addition, Foxd4l1.1 promotes inhibitory phosphorylation at the linker region of Smad1 and reduces Smad1 C-terminal activatory phosphorylation [13]. These results point to Foxd4l1.1 inhibiting target gene transcription at multiple levels.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…[13]. In addition, Foxd4l1.1 promotes inhibitory phosphorylation at the linker region of Smad1 and reduces Smad1 C-terminal activatory phosphorylation [13]. These results point to Foxd4l1.1 inhibiting target gene transcription at multiple levels.…”
Section: Introductionmentioning
confidence: 97%
“…Foxd4l1.1 (also known as Foxd5a/b) is an immediate-early neural marker whose expression begins under the BMP inhibited condition in the prospective neuroectoderm, which is necessary for maintaining neural stemness and neural induction [11,12]. We have shown that Foxd4l1.1 directly inhibits the ectodermal fate by binding to FRE (Foxd4l1.1 response element) within the ventx1.1 promoter region [13]. Foxd4l1.1 physically interacts with Xbra, and it blocks Xbra interacting with Smad1 to interact with and activate ventx1.1 transcription.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, Foxd4l1.1, an immediate early neural marker, was shown to be induced following inhibition of BMP signaling [153]. Foxd4l1.1 in naive neuroectoderm can induce expression of fgf8a/b in animal explants without xbra and fgf4 expression [153]. FGF8b contains Smad1 inactivation activity via linker region phosphorylation.…”
Section: Role Of Fgf In Neural Induction and Neuroectoderm Formationmentioning
confidence: 99%
“…The requirement of an FGF signal in addition to the inhibition of BMP for neuroectoderm specification remains to be clarified to resolve the long controversy between the neural induction and default neurogenesis models. In addition, FGF2, FGF4, FGF8, and Foxd4l1.1 may have different neural target genes but they share remarkable similarity in inhibiting BMP signaling for R-Smad(s) by generating inhibitory phosphorylation of the Smad linker region [55,123,139,149,153,158,160]. Collectively, FGF signaling is important for modulating BMP signaling in neural induction; however, additional details for various FGF ligands and their FGFRs and their individual mode of action are needed for a more complete picture to emerge.…”
Section: Role Of Fgf In Neural Induction and Neuroectoderm Formationmentioning
confidence: 99%